2014
DOI: 10.1002/2014ja020530
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the neutral‐ion coupling through 6 day planetary wave

Abstract: A westward 6 day oscillation with zonal wave number 1 is identified in the global maps of the ionospheric total electron content (TEC) during May 2003. This signature coincides with the wave activities in the mesosphere and lower thermosphere (MLT) region with a similar zonal structure and period, deduced from the temperature and wind observations from the Thermosphere Ionosphere and Mesosphere Electric Dynamics (TIMED) satellite. The vertical wavelength of this 6 day wave is estimated to be~65 km, which enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(65 citation statements)
references
References 32 publications
6
58
1
Order By: Relevance
“…The International Global Navigation Satellite System Service uses data from global GPS network to generate the global maps of TEC at 2.5° × 5° latitude‐longitude grids and 2‐hr universal time intervals (Mannucci et al, ). TEC data are broadly utilized to investigate ionospheric responses to the lower atmosphere through the planetary waves and solar tide waves (Chang et al, ; Gu, Dou, et al, ; Gu, Liu, et al, ; Liu et al, ; Wan et al, , ). The TEC during every Q6DW event recorded in section is analyzed to study the ionospheric responses.…”
Section: Data Set and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The International Global Navigation Satellite System Service uses data from global GPS network to generate the global maps of TEC at 2.5° × 5° latitude‐longitude grids and 2‐hr universal time intervals (Mannucci et al, ). TEC data are broadly utilized to investigate ionospheric responses to the lower atmosphere through the planetary waves and solar tide waves (Chang et al, ; Gu, Dou, et al, ; Gu, Liu, et al, ; Liu et al, ; Wan et al, , ). The TEC during every Q6DW event recorded in section is analyzed to study the ionospheric responses.…”
Section: Data Set and Methodsmentioning
confidence: 99%
“…This is because the ionospheric parameters are governed by geomagnetic lines and strongly influenced by solar fluxes, which makes the extraction of planetary wave signals more complicated. Therefore, the TEC observations at different local times are analyzed separately to exhibit the planetary wave signal more clearly, following Gu, Dou, et al (), Gu, Liu, et al (), and Liu et al ().…”
Section: Data Set and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oscillations of F region electron density with periods 2 and 6.5days are identified from midlatitude ground‐based observations and are assumed to be caused by TPWs [ Altadill and Apostolov , ]. Analyses of concurrent neutral dynamics and ionospheric observations provided further evidence linking planetary‐scale waves with ionospheric variability: Pancheva et al [] related QTDW observed in MLT neutral wind measurements to quasi‐2day oscillations of both F region electron density and ionospheric current; Gu et al [] found clear correspondence between 6day wave from temperature and wind measurements by Sounding of the Atmosphere using Broadband Emission Radiometry (SABER) and TIMED Doppler Interferometer (TIDI) on NASA's Thermosphere Ionosphere Mesosphere Energetics Dynamics (TIMED) satellites with 6day oscillation in total electron content (TEC). Ionospheric variabilities have also been related to TPWs (and also UFKWs) with periods between 5 and 6days identified in MLT neutral winds and in National Centers for Environmental Prediction (NCEP) reanalysis data [ Pancheva et al , ].…”
Section: Upper Atmosphere Variability As Related To Tides and Other Pmentioning
confidence: 99%
“…By diagnosing global data materials, Gu et al . [] showed 6 day oscillations in the total electron content (TEC), concurrent with the 6 day wave event in the mesosphere in May 2003. Meanwhile, Gan et al .…”
Section: Introductionmentioning
confidence: 99%